Institutional bases of state policy and legal activity in the sphere of environmental protection in emergency environmental situations - Azizov Tuxtamish Azamovich (Academia Open, 2019)
The article analyzes the institutional foundations of the political and legal activities of the state in the field of environmental protection in emergency environmental situations, as well as the issues of improving their activities.